Pleiotropic effects of the 3-hydroxy-3-methylglutaryl-CoA reductase inhibitors in pulmonary diseases: A comprehensive review. (February 2015) - Krishna, Rama K.; Issa, Omar; Saha, Debjit; Macedo, Francisco Yuri B.; Correal, Barbara; Santana, Orlando
Abstract: The 3-hydroxy-3-methylglutaryl-CoA reductase inhibitors (statins) are used extensively in the treatment of hyperlipidemia. They have also demonstrated a secondary benefit in a variety of other disease processes, actions which are known as pleiotropic effects. Review of the current pulmonary literature suggests a potential advantage of statin usage in a variety of pulmonary conditions. Our paper serves as a focused discussion on the pleiotropic effects of statins in the most common pulmonary disorders.